1997
DOI: 10.1038/sj.bjp.0701473
|View full text |Cite
|
Sign up to set email alerts
|

The pacemaker current If in single human atrial myocytes and the effect of β‐adrenoceptor and A1‐adenosine receptor stimulation

Abstract: 1 We used single human atrial myocytes to study I f occurrence, properties and pharmacological modulation. Cells were obtained by chunk enzymatic digestion from samples of right atrial appendages of patients undergoing corrective cardiac surgery. 2 Patch-clamped cells in the whole-cell con®guration were superfused with a modi®ed Tyrode solution to reduce contamination by interfering currents and to amplify I f . The average cell membrane capacitance was 85.06+2.41 pF (n=531). Data were consistent with the geom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
52
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 33 publications
9
52
0
Order By: Relevance
“…These cells are extremely small compared with cell diameters for sheep, horse, cow, and human cells in the present study. Other studies (36,37) have measured dimensions of human atrial myocytes from the right atrial appendage reporting values of 94.2 or 81 m length and 17.9 or 17 m width, which are in good agreement with a diameter of 17.3 Ϯ 1.2 m measured in the current study. The small cells in the study by Legato (27), obtained from an unspecified atrial region, may form part of the specialized sinoatrial node, and since we have shown a correlation between cell width and the presence of t tubules, perhaps in these small cells t tubules may not be needed.…”
Section: Discussionsupporting
confidence: 80%
“…These cells are extremely small compared with cell diameters for sheep, horse, cow, and human cells in the present study. Other studies (36,37) have measured dimensions of human atrial myocytes from the right atrial appendage reporting values of 94.2 or 81 m length and 17.9 or 17 m width, which are in good agreement with a diameter of 17.3 Ϯ 1.2 m measured in the current study. The small cells in the study by Legato (27), obtained from an unspecified atrial region, may form part of the specialized sinoatrial node, and since we have shown a correlation between cell width and the presence of t tubules, perhaps in these small cells t tubules may not be needed.…”
Section: Discussionsupporting
confidence: 80%
“…This indicated that native I f activates well within the diastolic voltage range of human atrial myocardium, which has been controversial on the basis of whole-cell measurements in recent years. 8,26 Thus, I f indeed might contribute to arrhythmogenesis in working myocardium.…”
Section: Native I F Activates Well In the Diastolic Voltage Range Of mentioning
confidence: 99%
“…However, I f is present in both automatic 1 and nonautomatic [2][3][4][5][6] regions of the heart, and the threshold voltage varies widely among cardiac regions, being least negative in sinus node (Ϫ40 mV in rabbit 7 ) and most negative in ventricle (Ϫ108 mV or more negative 5,8,9 ). Interestingly, I f activates at less negative voltages in newborn ventricle (Ϫ70 mV in rat 8,10 ).…”
mentioning
confidence: 99%